Testing the effectivity of different types of household greywater on irrigation of Marigold Plant - O'Yek, John David O.; Navarra, Nappy L. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
With the advent of water scarcity and the need for solutions to extend the usability of water, this study aims to determine household greywater sources that are appropriate for landscape irrigation by actual testing. Marigold plants were irrigated with seven different types of water: white water (WW), bath water stored equal or less tha 24 hours (BW=24), bath water stored equal or more than 25 hours, but less than 72 hours (BW=25), kitchen water stored equal or less than 24 hours (KW=24), kitchen water stored equal or more than 25 hours, but less than 72 hours (KW=25), laundry water stored equal or less than 24 hours (LW=24) and laundry water stored equal or more than 25 hours, but less than 72 hours (LW=25). The plants are irrigated with different greywater types for a period of thirty-five days and then documented and observed afterwards, using physical parameters such as quantity of flower heads, the color of heads of flowers, the size of heads of flowers, the shape of heads of flowers, the direction of heads of flowers, the color of leaves, the fullness of leaves, the height of plant, the plant mass, the root to shoot ratio and the fresh to dry weight ratio to gauge their growth and development. At the end of the test, it was found out that only bath water stored equal or less than 24 hours (BW=24) plants and bath water stored equal or more than 25 hours (BW=25) plants showed chance of survival.
includes appendices
Thesis (Master of Tropical Landscape Architecture) -- University of the Philippines Diliman
Keywords: Landscape irrigation; Water scarcity; Water conservation